2017
DOI: 10.4103/jehp.jehp_24_17
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion and dental caries experience among 8–9-year-old children in a city of South Indian region: A cross-sectional survey

Abstract: BACKGROUND:Although numerous studies have documented malocclusion in various age groups in India, the literature on the prevalence of malocclusion in mixed dentition is scanty. Dental caries is another most common condition affecting the general health. However, its association with malocclusion in mixed dentition is not well known.AIM:The purpose of this study was to establish the prevalence of malocclusion and its association with caries experience in 8–9-year-old children of Davangere city, South Indian reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 14 publications
3
10
2
2
Order By: Relevance
“…Variation in malocclusion can appear between age groups due to age and individual differences, or perhaps a shift from Class II malocclusion to the normal occlusion that occurs from the mesial movement of the first molars in the lower jaw where the second primary molars exfoliated 25 . The prevalence of normal occlusion was found low in the present study (18.9%) comparing with other studies by Alatrach et al, 29 (38.5%), Reddy et al, 22 (48.30%), Al-Zubair and Ghandour, 16 (69.4%), and Disha et al, 24 (59.1%). However, this result almost corresponds with the data in some other studies by Souza et al, 28 (16.7%).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Variation in malocclusion can appear between age groups due to age and individual differences, or perhaps a shift from Class II malocclusion to the normal occlusion that occurs from the mesial movement of the first molars in the lower jaw where the second primary molars exfoliated 25 . The prevalence of normal occlusion was found low in the present study (18.9%) comparing with other studies by Alatrach et al, 29 (38.5%), Reddy et al, 22 (48.30%), Al-Zubair and Ghandour, 16 (69.4%), and Disha et al, 24 (59.1%). However, this result almost corresponds with the data in some other studies by Souza et al, 28 (16.7%).…”
Section: Discussioncontrasting
confidence: 52%
“…There was statistic significant difference between the two age groups, which was found higher for age group 7-9 years old 42.0%, compared to the 10-12 years old 29.7%. By comparing with other studies, this result is much higher than that found by Disha et al, 24 study was crowding seen in 30.0% of school children (Table 5). This finding is almost in agreement with that of Almeida et al, 21 (31.59%), Al-Zubair and Ghandour, 16 (31.4%), Al-Zubair and Al-Almulla, 17 (30.4%), and by Yu et al, 26 (28.4%).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Malocclusion is characterized by the misalignment of teeth and dentofacial discrepancies. It has a moderate to high prevalence among children, regardless of the clinical malocclusion measure or dental index used (5)(6)(7)(8)(9)(10). There is evidence of a negative impact of malocclusion on OHRQoL (11)(12)(13)(14), although other research has not observed this (15,16).…”
mentioning
confidence: 99%